Comportamento antissocial online: uma abordagem pautada no modelo geral da agressão - Santos, Isabella Leandra Silva (2022)
The present research aimed to analyze antisocial online behavior (AOC) through the General Aggression Model (GAM), testing whether personality, antisocial online media and affective and cognitive variables impact this behavior. Thus, four studies were conducted. Study 1 aimed to carry out a systematic review of the literature on the theme, observing four categories of AOC: cyberbullying, cyberstalking, trolling and antisocial sexual behavior online. Study 2, subdivided into 2.1 (N = 215; 72.1% women; mean age = 26.58 years; SD = 7.84) and 2.2 (N = 214; 71.5% women; mean age = 23.57 years; SD = 7.04), sought to validate two measures, the Global Assessment of Internet Trolling Scale and the Antisocial Sexual Behavior Online Scale, which demonstrated adequate psychometric indices of validity and reliability. Study 3 (N = 397; 71% women; mean age = 29.3 years; SD = 8.54) sought to correlate the AOC, personality, exposure to antisocial content online and attitudes towards violence. The personality traits agreeableness and emotional stability were negatively related to the four behaviors. Finally, study 4 experimentally analyzed the impact of online antisocial content on the AOC, in addition to the role of personality and positive and negative affects in this model. A total of 302 volunteers participated (73.2% women; mean age = 26.57 years; SD = 8.87), divided into two groups. Multivariate effects of exposure on behavior, positive and negative affects were observed, and a model including personality, media, and affects in explaining behavior was significant. It is concluded that were tested distal and proximal aspects of GAM. The role of online media in the development of antisocial behavior is highlighted.